2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6944379
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of a plantar sensory evaluation system for early screening of diabetic neuropathy in a weight-bearing position

Abstract: The purpose of this study is to develop smart equipment to quantify plantar tactile sensibility for the early diagnosis and tracking of peripheral neuropathy caused by diabetes mellitus. In this paper, we offer a new testing system that is composed of a plantar tactile stimulation platform with a small moving contactor to stretch the skin tangentially, a response switch for each tactile stimulus, a motor control box, and a personal computer (PC) for psychophysical data processing. This quantitative sensory tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…According to the results of the tactile sensation test, the threshold at the fifth toe (Point 3) was higher than the other four points both for CS and non-CS groups. Ino et al [14] tested the plantar sensation at the same points in this research and observed that the fifth toe had the highest plantar detection threshold, followed by the first metatarsal head. Surprisingly, we observed that young females with CS had a lower tactile threshold at the foot sole, opposite to the findings in the previous study.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…According to the results of the tactile sensation test, the threshold at the fifth toe (Point 3) was higher than the other four points both for CS and non-CS groups. Ino et al [14] tested the plantar sensation at the same points in this research and observed that the fifth toe had the highest plantar detection threshold, followed by the first metatarsal head. Surprisingly, we observed that young females with CS had a lower tactile threshold at the foot sole, opposite to the findings in the previous study.…”
Section: Discussionmentioning
confidence: 71%
“…In this research, five plantar points were selected as test points. To eliminate serial effects, the stimulation order was set as 1: first toe, 2: heel, 3: fifth toe, 4: first metatarsal head, 5: fifth metatarsal head [14]. White circles denote the test points, and the dotted line with a single arrow denotes the stimuli order.…”
Section: Plantar Cutaneous Sensation Testmentioning
confidence: 99%
“…The author also observed leaning on stimulation site and velocity and a dissimilarity in the maximum level between normal patients and patients with an early detection of nerve damage. [19] In this study, author try to assess patients with diabetic peripheral neuropathy using vibrations generated from a mobile phone. Total 61 patients were tested with three different techniques the first is using 10 g Semmes Weinstein, second is tuning fork, and the third is mobile phone generated vibration.…”
Section: B Tuning Forkmentioning
confidence: 99%